Russia-Israel relationship transformed by Syria conflict : political interests overshadow social and economic ties - Averbukh, Lidia; Klein, Margarete (2018)
Zusammenfassung: Recent months have witnessed a warming of relations between Russia and Israel. One indicator of the trend is the frequency of high-level meetings, culminating in Prime Minister Netanyahu’s participation - as the only Western state guest - in the military parade on Red square on 9 May. Alongside existing social ties and economic cooperation, the prospect of a recalibration of Russian policy in Syria to take greater account of Israeli security interests has been another important driver. Nevertheless, the Russian-Israeli relationship remains constrained and volatile. For Moscow it is just one element of a multivectoral Middle East policy